The impact of financial restatements on financial markets: a systematic review of the literature - Fragoso, João Luís Ferro do Rosário (2018)
This dissertation reviews the literature systematically regarding the impact of financial restatements on financial markets and identifies some research avenues that can be explored in future empirical work. This accounting event is a clear case of bad news and affects several market participants. The methodology employed is the systematic review of the literature that aims at minimising the weaknesses and biases of the traditional literature review. One of the most robust conclusions is that the short-term market reaction to the disclosure of a restatement varies between 1.4% and 20%. The magnitude of the impact depends on the cause and reason for the restatement, who initiates it, if there is litigation and if there is fraud. In the long-term, it is not clear if the market fully assimilates the information contained in a financial restatement. There is also evidence that the market anticipates the publication of a financial restatement given the significant and negative abnormal returns in the pre-event period. Also, the short-selling activity increases in the pre-event period and during the days surrounding the disclosure of such accounting event. Together, these findings suggest that market participants can anticipate this event. Moreover, financial restatement firms experience an increase in the cost of capital, an increase in the cost of debt, a decrease in the reputation of the company and cause a contagious effect on other firms operating in the same industry. The results of this systematic review emphasise that the market impact of financial restatements is a relevant topic in the accounting and finance domain and there are some research avenues that may be explored in further empirical work related to the longterm dynamics of financial markets and the role of some sophisticated agents in the phenomenon.